Infectious human adenoviruses are shed in urine even after disappearance of urethral symptoms - Hanaoka, Nozomu; Ito, Shin; Konagaya, Masami; Nojiri, Naomi; Yasuda, Mitsuru; Fujimoto, Tsuguto; Deguchi, Takashi (PloS one, 2019)
Urethritis is a common sexually transmitted disease, and human adenoviruses (HAdVs) have been found to be associated with nonchlamydial nongonococcal urethritis. However, the level and viability of HAdV in the urine of patients with urethritis remain unclear. Male patients with urethritis and an asymptomatic group were screened using their First-void urine (FVU) for urethritis-related pathogens to identify those with HAdV DNA. FVU and gargle fluid were collected from all patients including from those in the asymptomatic group. A swab of eye discharge was also collected from patients with eye symptoms. The pharyngeal and/ or ocular fluid was also screened only in cases in which FVU was positive for HAdV DNA. HAdVs were isolated using A549 cell lines and typed by sequencing, and viral shedding during 2 years was quantified using real-time PCR. The prevalence of HAdV was assessed in the urethritis and asymptomatic groups, and viral load, isolated HAdV types, and urethral symptoms were compared between the groups. The positive detection rate of HAdV DNA was significantly higher in the urethritis group than in the asymptomatic group. Of 398 patients with urethritis, HAdV was isolated in all 32 cases (23 cases in which only HAdV DNA was detected with a mean of 2 × 109 copies/mL in urine samples). Of 124 control cases, one had HAdV monoinfection. The most frequently detected HAdV type was 56, followed by types 37 and 64. Regarding the relationship between symptoms and isolated HAdVs, the virus was isolated for up to 12 days after urethritis symptoms disappeared. HAdVs were significantly detected and isolated from the FVU of patients with urethritis. Furthermore, high levels of infectious HAdVs are excreted in urine for a long period even after urethritis symptoms disappear.